Potensi Penerapan Green Accounting Masa Depan melalui Perspektif Paradigma Positivisme - Syarifuddin, Muhammad; Khomsiyah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Green accounting has become a major concern in contemporary accounting literature to integrate information related to environmental and social externalities into organizational reporting systems. This article aims to analyze the potential and challenges of implementing green accounting in the future through the lens of the positivism paradigm. Through a literature review, this paper discusses the concept of the Khun paradigm and Auguste Comte's positivism to provide a philosophical basis for the development of green accounting. In addition, based on the empirical study of the article, findings related to the current implementation of green accounting, the challenges and obstacles faced, as well as potential strategies to ensure successful implementation in the future are also discussed. The results of the literature review show the need for consistent standardization by regulators to encourage widespread adoption of green accounting. Apart from that, the use of digital technology and collaboration between various stakeholders is the key to the successful implementation of green accounting in the future in achieving sustainable development goals.